Medium-temperature curing conductive silver paste and preparation method and application thereof
By optimizing the composition of silver powder and resin in a medium-temperature curing conductive silver paste, the problems of insufficient conductivity and adhesion in existing technologies have been solved, achieving high conductivity and adhesion on heat-sensitive substrates and meeting the needs of high-end electronic products.
Patent Information
- Application Number
- CN202511070267.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-11-14
AI Technical Summary
Existing medium-temperature curing silver pastes have insufficient conductivity and adhesion on heat-sensitive substrates, making it difficult to meet the requirements of high-end electronic products.
Medium-temperature curing conductive silver paste is composed of silver powder, glass powder, organic solvent and polymer resin in a specific ratio. By adjusting the proportion of silver powder and selecting different resins, conductivity and adhesion are improved, and defoamer and curing agent are used to enhance performance.
The prepared conductive silver paste exhibits good adhesion and conductivity on PET film, with low resistivity, meeting the requirements for use on heat-sensitive substrates.
Smart Images

Figure CN120954778A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of conductive silver paste technology, and relates to a high conductivity silver paste suitable for printed electronics, flexible circuits and photovoltaic electrodes, specifically to a medium-temperature curing conductive silver paste, its preparation method and application. Background Technology
[0002] With the development of the electronics industry and the continuous improvement of the integration of electronic products, new applications have placed higher demands on the internal stress, adhesion, thermal conductivity, and electrical properties of electronic device packaging materials. Conductive silver paste, as an adhesive that combines excellent conductivity and strong adhesion, also possesses characteristics such as environmental friendliness, low resistivity, fine pitch, high bonding strength, low curing temperature, strong weather resistance, and strong mechanical properties. It is widely used in high-end fields such as electronics, integrated circuits, electromagnetic wave shielding, and antistatic applications. In practical applications, conductive silver paste needs to be cured or sintered to form an electrode film on the substrate. Currently, existing conductive silver pastes on the market typically require high-temperature sintering (>200℃) to obtain high conductivity, which is difficult to meet the practical needs of heat-sensitive substrates (such as PET / PI films). While existing medium-temperature curing silver pastes (curing temperature 100~200℃) are compatible with plastic substrates, they generally suffer from insufficient conductivity, poor adhesion, and long curing times, further affecting their service life. These shortcomings limit the use of medium-temperature conductive silver pastes in many fields.
[0003] In view of this, the present invention is hereby proposed. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a medium-temperature curing conductive silver paste, its preparation method, and its application.
[0005] To achieve the above objectives, the present invention provides the following technical solution: On one hand, the present invention provides a medium-temperature curing conductive silver paste, which, by mass percentage, comprises the following components: 60-80% silver powder, 1-8% glass powder, 10-30% organic solvent, 0.1-8% polymer resin, and the balance being additives; wherein the polymer resin is one of polyester resin, polyurethane resin, o-cresol epoxy resin, acrylic resin, and vinyl chloride resin.
[0006] Specifically, the organic solvent is a mixture of any two of DBE (divalent ester), xylene, and PMA (propylene glycol methyl ether acetate).
[0007] Specifically, the silver powder is flake-shaped silver powder with a particle size of 1~10μm.
[0008] Specifically, the silver powder includes silver powder A and silver powder B, with the ratio of silver powder A to silver powder B being 1:3. The particle size of silver powder A is 1~5μm, and the particle size of silver powder B is 5~10μm.
[0009] Specifically, the glass powder has a particle size of 1~10μm.
[0010] Specifically, the additives are defoamers and curing agents, wherein the defoamer is tributyl phosphate and the curing agent is triethanolamine.
[0011] On the other hand, the present invention provides a method for preparing the medium-temperature curing conductive silver paste as described above, comprising the following steps: Step 1: Weigh out the silver powder, glass powder, organic solvent, polymer resin, and additives according to their mass percentages. Step 2: Add the organic solvent, polymer resin, and additives to a container, and stir evenly at a specific temperature to obtain an organic carrier solution; Step 3: First, pour the silver powder, glass powder and organic carrier solution into a mortar and stir evenly, then grind for a specific time to obtain the desired conductive silver paste.
[0012] Specifically, in step 2, the mixture is mechanically stirred at room temperature for 2-3 hours, with the stirring speed being 800-1000 r / min.
[0013] Specifically, in step 3, mechanically stir for 30 minutes, then grind with a three-roll mill 3 to 7 times, each time for 4 to 5 minutes, with the total grinding time controlled within half an hour.
[0014] In another aspect, the present invention provides an application of the medium-temperature curing conductive silver paste as described above, as an application of the conductive material in a heat-sensitive substrate.
[0015] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: This invention utilizes different resin and solvent ratios to address the poor conductivity and adhesion issues of existing medium-temperature curing silver pastes. Because different resins contain varying levels of polar and conjugated groups, the adhesion of the prepared conductive silver paste to PET films differs. The conductivity is improved by adjusting the silver powder ratio. Ultimately, the conductive silver paste prepared with acrylic resin exhibits better adhesion and conductivity. This is attributed to the fact that acrylic resin contains fewer polar groups compared to other resins and its molecular chains are linear. After curing, the distance between silver powder particles decreases, resulting in a lower resistivity; the volume resistivity of the conductive silver paste reaches 7.35 × 10⁻⁶. -5 Ω·cm. Attached Figure Description
[0016] The accompanying drawings are incorporated in and form part of this specification, and together with the description serve to explain the principles of the invention.
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a flowchart of the preparation method of the present invention. Detailed Implementation
[0019] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples consistent with some aspects of the invention as detailed in the appended claims.
[0020] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0021] In the following examples, 325-mesh glass powder with a melting point of 400°C was used.
[0022] Example 1 See Figure 1 As shown in the figure, this embodiment provides a method for preparing a medium-temperature curing conductive silver paste, as detailed below: Step 1: Weigh the raw materials by mass percentage: 60% silver powder (silver powder A and silver powder B are mixed in a 1:3 ratio), 8% glass powder, 30% organic solvent (22% xylene and 8% divalent ester), 0.1% polymer resin, and the remainder is additives; wherein the polymer resin is polyester resin, the silver powder is flake silver powder, the diameter of silver powder A is 4.5μm, and the diameter of silver powder B is 8μm; the additives are defoamer (2% tributyl phosphate) and curing agent (3% triethanolamine).
[0023] Step 2: Add the organic solvent, polymer resin and additives to the container respectively, and stir mechanically at 1000 r / min at room temperature for 2 hours to obtain the organic carrier solution.
[0024] Step 3: First, pour the silver powder, glass powder and organic carrier solution into a mortar and stir mechanically. Stir at 1000 r / min for 30 min, then grind three times with a three-roll mill for 5 min each time to obtain the desired conductive silver paste A.
[0025] Example 2 This embodiment provides a method for preparing a medium-temperature curing conductive silver paste, as detailed below: Step 1: Weigh the raw materials by mass percentage: 70% silver powder (silver powder A and silver powder B are mixed in a 1:3 ratio), 6% glass powder, 20% organic solvent (18% divalent ester and 2% propylene glycol methyl ether acetate), 1.5% polymer resin, and the remainder is additives; wherein the polymer resin is polyurethane resin, the silver powder is flake silver powder, the diameter of silver powder A is 4.5μm, and the diameter of silver powder B is 8μm; the additives are defoamer (2% tributyl phosphate) and curing agent (3% triethanolamine).
[0026] Step 2: Add the organic solvent, polymer resin and additives to the container respectively, and stir mechanically at 800 r / min at room temperature for 3 hours to obtain the organic carrier solution.
[0027] Step 3: First, pour the silver powder, glass powder and organic carrier solution into a mortar and stir mechanically. Stir at 900 r / min for 30 min, then grind 7 times with a three-roll mill for 4 min each time to obtain the desired conductive silver paste B.
[0028] Example 3 This embodiment provides a method for preparing a medium-temperature curing conductive silver paste, as detailed below: Step 1: Weigh the raw materials by mass percentage: 68% silver powder (silver powder A and silver powder B are mixed in a 1:3 ratio), 4% glass powder, 15% organic solvent (9% xylene and 6% propylene glycol methyl ether acetate), 5% polymer resin, and the remainder is additives; wherein the polymer resin is o-crestoform epoxy resin, the silver powder is flake silver powder, the diameter of silver powder A is 4.5μm, and the diameter of silver powder B is 8μm; the additives are defoamer (2% tributyl phosphate) and curing agent (3% triethanolamine).
[0029] Step 2: Add the organic solvent, polymer resin and additives to the container respectively, and stir mechanically at 900 r / min at room temperature for 2.5 h to obtain the organic carrier solution.
[0030] Step 3: First, pour the silver powder, glass powder and organic carrier solution into a mortar and stir mechanically. Stir at 800 r / min for 30 min, then grind four times with a three-roll mill for 5 min each time to obtain the desired conductive silver paste C.
[0031] Example 4 This embodiment provides a method for preparing a medium-temperature curing conductive silver paste, as detailed below: Step 1: Weigh the raw materials by mass percentage: 65% silver powder (silver powder A and silver powder B are mixed in a 1:3 ratio), 5% glass powder, 10% organic solvent (6% divalent ester and 4% propylene glycol methyl ether acetate), 8% polymer resin, and the remainder is additives; wherein the polymer resin is acrylic resin, the silver powder is flake silver powder, the diameter of silver powder A is 4.5μm, and the diameter of silver powder B is 8μm; the additives are defoamer (2% tributyl phosphate) and curing agent (3% triethanolamine).
[0032] Step 2: Add the organic solvent, polymer resin and additives to the container respectively, and stir mechanically at 1000 r / min at room temperature for 2 hours to obtain the organic carrier solution.
[0033] Step 3: First, pour the silver powder, glass powder and organic carrier solution into a mortar and stir mechanically. Stir at 1000 r / min for 30 min, then grind with a three-roll mill 6 times, 5 min each time, to obtain the desired conductive silver paste D.
[0034] Example 5 This embodiment provides a method for preparing a medium-temperature curing conductive silver paste, as detailed below: Step 1: Weigh the raw materials by mass percentage: 80% silver powder (silver powder A and silver powder B are mixed in a 1:3 ratio), 1% glass powder, 12% organic solvent (9% xylene and 3% propylene glycol methyl ether acetate), 5% polymer resin, and the remainder is additives; wherein the polymer resin is chloroacetic acid resin, the silver powder is flake silver powder, the diameter of silver powder A is 4.5μm, and the diameter of silver powder B is 8μm; the additives are defoamer (2% tributyl phosphate) and curing agent (3% triethanolamine).
[0035] Step 2: Add the organic solvent, polymer resin and additives to the container respectively, and stir mechanically at 900 r / min at room temperature for 2 hours to obtain the organic carrier solution.
[0036] Step 3: First, pour the silver powder, glass powder and organic carrier solution into a mortar and stir mechanically. Stir at 900 r / min for 30 min, then grind 5 times with a three-roll mill for 5 min each time to obtain the desired conductive silver paste E.
[0037] To further verify the effectiveness of the technical solution provided by this invention, the following tests were performed on conductive silver paste A, conductive silver paste B, conductive silver paste C, conductive silver paste D, conductive silver paste E, and conductive silver paste F respectively: (1) Adhesion test Silver paste was cured onto a PET film, and adhesion was tested according to peel grade standards. An ACE-QFH cross-cut adhesion tester was used to test the adhesion of the samples. The cross-cut adhesion tester was used to scratch the coating in both longitudinal and transverse directions. 3M tape was then applied to the entire scratched area, and the tape was peeled off at a uniform speed at a 30° upward angle. After testing, the coating was classified into six grades: 5B, 4B, 3B, 2B, and 1B, to determine the coating adhesion.
[0038] (2) Conductivity test The resistivity of the cured silver paste was tested using a DC resistance meter to assess its conductivity. The resistivity was used for characterization, and the calculation formula is as follows: ρ = RWd / L In the formula: ρ is resistivity, Ω·cm; R is resistance, Ω; W is line width; d is coating thickness after curing; L is the length of the cured coating line.
[0039] The specific test results are shown in Table 1.
[0040] Table 1 In summary, the test results in Table 1 show that the silver pastes in Examples 2 and 4 exhibit excellent adhesion, indicating that polyurethane and acrylic resins can both bond well with silver powder particles and show good adhesion to the PET substrate. This is because the numerous chemical bonds contained in the resins increase electrostatic attraction and form intermolecular forces with the substrate. During the curing process, the ester groups gradually become active, thus cross-linking with the substrate and exhibiting good adhesion. The resistivity data shows that after curing, Examples 1 and 2 have higher resistivity due to the presence of polar groups and conjugated structures in the polyester and polyurethane resin matrices. Cross-linking reactions occur between molecules during curing, resulting in relatively small volume shrinkage. The conductive silver paste prepared with acrylic resins exhibits better adhesion and conductivity. This is attributed to the fact that acrylic resins contain fewer polar groups compared to other resins and have straight molecular chains. After curing, the distance between silver powder particles decreases, resulting in lower resistivity. The volume resistivity of the conductive silver paste reaches 7.35 × 10⁻⁶. -5 Ω·cm; In summary, the conductive silver pastes prepared in Examples 1-5 of this invention all exhibited adhesion strength greater than or equal to 3 after adhesion testing, and resistivity less than or equal to 22.5 × 10⁻⁶ after conductivity testing. -5 The Ω·cm values all meet the requirements for use as conductive materials in heat-sensitive substrates.
[0041] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention.
[0042] It should be understood that the present invention is not limited to the content already described above, and various modifications and changes can be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A medium-temperature curing conductive silver paste, characterized in that, The product comprises the following components by mass percentage: 60-80% silver powder, 1-8% glass powder, 10-30% organic solvent, 0.1-8% polymer resin, and the balance being additives; wherein the polymer resin is one of polyester resin, polyurethane resin, o-cresol epoxy resin, acrylic resin, and vinyl chloride resin.
2. The medium-temperature curing conductive silver paste according to claim 1, characterized in that, The organic solvent is a mixture of any two of DBE, xylene, and PMA.
3. The medium-temperature curing conductive silver paste according to claim 1, characterized in that, The silver powder is in the form of flakes, and the particle size of the silver powder is 1~10μm.
4. The medium-temperature curing conductive silver paste according to claim 3, characterized in that, The silver powder includes silver powder A and silver powder B, with the ratio of silver powder A to silver powder B being 1:
3. The particle size of silver powder A is 1~5μm, and the particle size of silver powder B is 5~10μm.
5. The medium-temperature curing conductive silver paste according to claim 1, characterized in that, The glass powder has a particle size of 1~10μm.
6. The medium-temperature curing conductive silver paste according to claim 1, characterized in that, The additives are a defoamer and a curing agent, wherein the defoamer is tributyl phosphate and the curing agent is triethanolamine.
7. A method for preparing medium-temperature curing conductive silver paste according to any one of claims 1 to 6, characterized in that, Includes the following steps: Step 1: Weigh out the silver powder, glass powder, organic solvent, polymer resin, and additives according to their mass percentages. Step 2: Add the organic solvent, polymer resin, and additives to a container, and stir evenly at a specific temperature to obtain an organic carrier solution; Step 3: First, pour the silver powder, glass powder and organic carrier solution into a mortar and stir evenly, then grind for a specific time to obtain the desired conductive silver paste.
8. The method for preparing the medium-temperature curing conductive silver paste according to claim 7, characterized in that, In step 2, the mixture is mechanically stirred at room temperature for 2-3 hours, with a stirring speed of 800-1000 r / min.
9. The method for preparing the medium-temperature curing conductive silver paste according to claim 7, characterized in that, In step 3, first mechanically stir for 30 minutes, then use a three-roll mill to grind 3 to 7 times, each time for 4 to 5 minutes, and control the total grinding time to within half an hour.
10. The application of the medium-temperature curing conductive silver paste according to any one of claims 1 to 6, characterized in that, Application of conductive materials in heat-sensitive substrates.
Citation Information
Patent Citations
Middle and low temperature curing conductive silver slurry
CN101373646A
Low-temperature solidifying environment-friendly conductive silver paste and preparation method thereof
CN103094662A
Conductive silver paste and preparation method thereof
CN114283964A
Conductive paste composition
JP2004111057A
Conductive paste composition, and manufacturing method of electrode using the composition
JP2010161062A
